Improving Table Tennis Learning Outcomes Through the Part Method Approach to Students - Jonas Solissa (International Journal of Education, Information Technology, and Others, 2022)
This study aims to improve the learning outcomes of table tennis through the student section method approach. The research was conducted on students of Physical Education, Health and Recreation, Patimura University, Ambon, in 2021. Using the type of classroom action research (CAR). The instrument used for data collection is observation and performance test of basic table tennis technical skills (Rubric for Assessment). Based on the results of this research data, it shows that the application of the part method in table tennis learning has a positive impact on improving students' learning abilities, this can be seen from the absorption of students increasing from the first cycle by 66.74% (13 students from 34 students have finished studying) and the second cycle increased to 83.79.%. In the second cycle, classical student learning completeness has been achieved. This means that the success indicators have been achieved as expected by researchers and table tennis lecturers